A strategic model of macro-economic and supply chain factors that influence the decision-making process of SA retailers when expanding their footprint in African countries - Engelbrecht, Lizet (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.